RECREATIONAL WATERFRONT HARBOUR DI BANTEN DENGAN PENEKANAN ANALOGI ARSITEKTUR - Nia Damayanti; Agung Kumoro; Hari Yuliarso (ARSITEKTURA, 2015)
Designing Recreational Waterfront Harbour in Banten motivated by the lack of ports in Banten, the issue of the Selat Sunda bridge construction plan, and the tourism potential of the waterfront, so the purpose of this scheme is to get the port design that can provide berthing facilities and activities waterfront recreational activities by applying Architecture Analogy Emphasis  to express the shape and movement of water in buildings and harbor area. Design issues are: how the expression form and movement of water can be translated into the design of Recreational Waterfront Harbour. The method used in the design of mass system design, the basic shape and appearance of the harbor is the analogy architectural method of shapes and movement of water. The result obtained is the design of a blend of a port area and waterfront recreation area that expresses the shape and movement of water in the form of basic, mass system and display area. Keywords: Recreational Waterfront, Form and Movement Water, Architecture Analogy.